Factors Affecting the Performance of Generation Z Workforce Employees: Analysis of Work Life Balance, Leadership Style and Organizational Culture - Setyo Widodo, Djoko; Maghfuriyah, Alfi (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Literature review research on factors affecting employee performance of Generation Z workforce: Analysis of Work Life Balance, Leadership Style and Organizational Culture is a scientific literature article in the scope of human resource management science. The purpose of this literature research is expected to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of human resource management. The approach used in this study is descriptive qualitative. The data collection technique uses literature studies. The data used in this descriptive qualitative approach comes from previous research that is relevant to this study and is sourced from academic online media such as the Scopus Elsevier Journal, Emerald, Sage, WoS, Reputable National Journal (SINTA), DOAJ, EBSCO, Google Scholar and digital reference books. The results of this literature review article include: 1) Work Life Balance affects the Performance of Generation Z Workforce Employees; 2) Leadership Style affects the Performance of Generation Z Workforce Employees; and 3) Organizational Culture affects the Performance of Generation Z Workforce Employees.